EFFECTS OF THEAFLAVINS ON GASTRIC CANCER CELL LINE - Roy, Surmi; Saha, Arpita; Chatterjee, Ananya; Chatterjee, Sirshendu; Mazumder, Santasree; Bandyopadhyay, Sandip K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The objective of this study was to evaluate the anticarcinogenic effects of theaflavins (TFs), component of black tea, on human gastric cancer cell line. Materials and Methods: Cell viability was assessed by WST-1 reagent. Acridine orange (AO) and ethidium bromide (EB) fluorescence staining method were used to detect apoptotic cells, if any, followed by flow cytometric detection. To evaluate the molecular basis for understanding the apoptotic pathway, reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were measured. Pro- and anti-apoptotic protein and gene expressions were detected by western blot and real-time techniques. Results: TFs-treated AGS cell indicated apoptosis-mediated cell death. The presence of TFs induced the generation of ROS and which in turn changes the MMP with the elevated level of cyt c, activation of caspase-9, caspase-3, and PARP cleavage. Our study also showed that TFs treatment altered the Bax/Bcl2 ratio and upregulated the expression of p53. Conclusion: All these observations lead to the fact that TFs developed potential chemopreventive effects through the induction of apoptosis through mitochondria-mediated death cascade in the human gastric cancer cell.